On the Simulation of Two‐dimensional Electronic Spectroscopy of Indole‐containing Peptides1. (14th July 2017) - Giussani, Angelo; Marcheselli, Jacopo; Mukamel, Shaul; Garavelli, Marco; Nenov, Artur
Abstract: A benchmark study of low‐cost multiconfigurational CASSCF/CASPT2 schemes for computing the electronic structure of indole is presented. This facilitates the simulation of near‐ultraviolet (UV) pump visible (VIS) probe ( i.e . two‐color) two‐dimensional electronic spectra (2DES) of homo‐ and hetero‐aggregates as well as for processing of multiple snapshots from molecular dynamics simulations. Fingerprint excited‐state absorption signatures of indole are identified in a broad spectral window between 10 and 25 k cm −1 . The 18–24 k cm −1 spectral window which has no absorption of the monomer and noninteracting aggregates is ideally suited to embed charge‐transfer signatures in stacked aggregates. The small peptide Trp‐cage, containing a tryptophan and a tyrosine amino acids, having indole and phenol as side chains, respectively, serves to prove the concept. Clear charge‐transfer signatures are found in the proposed spectral window for an interchromophore distance of 5 Å making near‐UV pump VIS probe 2DES a suitable technique for resolving closely packed aggregates. We demonstrate that 2DES utilizing ultra‐short pulses has the potential to resolve the nature of the spectroscopically resolved electronic states and that the line shapes of the excited‐state absorption signals can be correlated to the polarity of the relevant states. Abstract : A benchmark study of low‐cost multiconfigurational CASSCF/CASPT2 schemes for computing the electronic structure of indole is presented. The best‐performing scheme is then applied to an unfolded configuration and to a folded configuration of the 20‐residue‐long polypeptide Trp‐cage, containing the amino acids tryptophan and tyrosine, in order to study the applicability of bidimensional electronic spectroscopy (2DES) for resolving closely packed aggregates. We demonstrate that 2DES utilizing ultra‐short pulses has the potential to resolve the nature of the spectroscopically resolved electronic states and that the line shapes of the excited state absorption signals can be correlated to the polarity of the relevant states.